2019
DOI: 10.2136/sssaj2018.05.0169
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Cd2+/Cr3+ During Aqueous Fe(II)‐Induced Recrystallization of Al‐Substituted Goethite

Abstract: Recrystallization of Al‐goethites affected mobility of heavy metals in soils. Co‐existing Cd2+/Cr3+ decreased the Fe atom exchange rates between Fe2+aq and Al‐goethites. Fe2+aq‐induced recrystallization of Al‐goethites stabilized Cd2+ and Cr3+. More Cr3+ are stabilized due to its similar ionic radius with Fe3+ and Al3+. Cd2+ ions more active than Cr3+ considering iron mineral activity in soils. The aqueous Fe2+ (Fe2+aq)–induced recrystallization of iron minerals is an important geochemical process with critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Interactions between Fe and OM enhance the Cd adsorption, complexation, and redox reactions in a rice field. It was reported that Fe atoms were exchanged between Fe 2+ and structural Fe 3+ in Al-substituted goethites, which decrease Cd 2+ by exchange rates, with partial Cd 2+ ions stabilized. The Cd 2+ ions were immobilized as a result of the hydrolysis constant of Cd 2+ as well as the ionic radius with Fe 3+ and Al 3+ , in recrystallized Al-substituted goethites.…”
Section: Chemistry Of CD In Agricultural Soilmentioning
confidence: 99%
“…Interactions between Fe and OM enhance the Cd adsorption, complexation, and redox reactions in a rice field. It was reported that Fe atoms were exchanged between Fe 2+ and structural Fe 3+ in Al-substituted goethites, which decrease Cd 2+ by exchange rates, with partial Cd 2+ ions stabilized. The Cd 2+ ions were immobilized as a result of the hydrolysis constant of Cd 2+ as well as the ionic radius with Fe 3+ and Al 3+ , in recrystallized Al-substituted goethites.…”
Section: Chemistry Of CD In Agricultural Soilmentioning
confidence: 99%